Controlled sintering and phase transformation of yttria-doped tetragonal zirconia polycrystal material. Issue 19 (1st October 2021) - Li, Qiannan; Hao, Xiandong; Gui, Yuxi; Qiu, Hongju; Ling, Yeqing; Zheng, Hewen; Omran, Mamdouh; Gao, Lei; Chen, Jin; Chen, Guo
Abstract: In this paper, 3 mol% yttria-doped tetragonal zirconia polycrystal material (3 mol% Y2 O3 –ZrO2 ) was prepared using an optimised pressureless sintering process. The phase change and particle size distribution of Y2 O3 –ZrO2 during sintering were studied, and the effect of sintering temperature on the properties of Y2 O3 –ZrO2 was analysed. The raw materials and prepared samples were analysed using XRD, Raman spectroscopy, SEM, and Gaussian mathematical fitting. The results show that sintering encourages the transformation of the monoclinic phase into the tetragonal phase, thus improving the crystallinity of the sample. The relative content of the tetragonal phase in the sample increased from 57.43% to 99.80% after sintering at 1200 °C for 1 h. In the range of sintering temperatures studied in this paper (800–1200 °C), the zirconia material sintered at 1000 °C presented the lowest porosity and the best density.